Research and Implementation of Bluetooth Indoor Auto-tracking System - Chen, Yen-Jen; Zheng, Kai-Wen (Discoveries in Agriculture and Food Sciences, 2019)
In recent years, outdoor positioning technology has been widely used and indoor positioning technology has gradually matured. Relevant applications such as: Indoor Location Based Service, Ambient Assistant Living, Indoor Navigation, Location Based Advertising, and the like have begun to show up in daily life and bring people with diversity and rich service content. The proposed study focuses on the research of real-time indoor dynamic positioning and dynamic tracking related mechanisms and algorithms, and uses the “microcontroller module” and “Bluetooth communication module” to actually detect the operational mechanism of the Bluetooth dynamic positioning system. This prototype system uses the smart phone as the locator of the traced person, named tracee (a new word created in this paper). The three-wheeled carrier acts as the tracer’s body. On the locator, the processor is used to dynamically calculate the dynamic positioning of the tracee, and the calculated positioning result is transmitted to the tracer through the Bluetooth. The tracer calculates the distance and orientation, and then controls the axle motor so that the three-wheeled carrier closely follows the smart phone. Although many self-propelled vehicles have been sold on the market at present, and most of the follow-up signal uses infrared rays, ultrasonic waves, or Wi-Fi to complete the tracking action. However, the first two signals often require the tracee to carry an additional signal transmission device so as to assist in tracking. Due to the current popularity of mobile phones, although Wi-Fi and Bluetooth chips are already installed on the phone, yet the power consumption of Wi-Fi is still much higher than that of the Bluetooth. Therefore, in this study, Bluetooth was used to complete the indoor positioning system. Bluetooth belongs to 2.4GHz wireless technology; when using the Bluetooth signal for tracking, the signal strength is likely to cause many noises due to shielding, signal diffraction, or reflection, resulting in a deviation between the calculated transmission distance and the actual distance. The purpose of this study is to design a prototype of an Indoor Automatic Tracking System (hereafter named IATS) and explorer how to reduce the Bluetooth signal strength deviation so as to improve the accuracy of positioning is the main object of this study.